The Effect of Public Insurance Coverage for Childless Adults on Labor Supply - Laura Dague; Thomas DeLeire; Lindsey Leininger (Institute for the Study of Labor (IZA), 2014)
This study provides plausibly causal estimates of the effect of public insurance coverage on the employment of non-elderly, non-disabled adults without dependent children ("childless adults"). We use regression discontinuity and propensity score matching difference-in-differences methods to take advantage of the sudden imposition of an enrollment cap, comparing the labor supply of enrollees to eligible applicants on a waitlist. We find enrollment into public insurance leads to sizable and statistically meaningful reductions in employment up to at least 9 quarters later, with an estimated size of from 2 to 10 percentage points depending upon the model used.
Keywords: I13; J22; 330; health insurance; labor supply